(untitled) (Herald of Journalism, 2018)
In the scientific literature, national character is regarded as historically constituted a set of stable psychological traits of representatives of a nation that define the usual manner of their behavior and the typical course of action, and manifested in their relation to social and domestic environment, the outside world, work to his and others ethnic communities.However, this problem is not actively considered in the comparative aspect, in this regard, this article attempts to provide a means of verbalization of the concept of appreciation in Russian and French. Key words: national character, mentality, national mentality, the language, the concept of «gratitude» linguistics.